Lingvističeskij kiberpank v russkom Internete: funkcii i vidy jazykovoj igry s anglijskimi zaimstvovanijami - Mečkovskaja, Nina Borisovna (Slavistična revija, 2007)
The author demonstrates that in Russian computer -Internet slang, play with English terms facilitates adoption of borrowings, maintains Russian-English computer bilingualism, improves users' metalinguistic reflection, satisfies their nedd for artistic-aesthetic expression, and help with relieving emotions. The examples of language play are categorized in terms of the graphic and lexical-phraseological planes.
Keywords: angleščina; angleške izposojenke; English borrowings; English language; informacijske tehnologije; information technologies; internet; jezikovna dinamika; Russian language; ruščina; substandardne variante jezika; technical language